Global wave hindcast with Australian and Pacific Island Focus: From past to present. (14th August 2020) - Smith, Grant A.; Hemer, Mark; Greenslade, Diana; Trenham, Claire; Zieger, Stefan; Durrant, Tom
Abstract: Wind‐wave hindcast data have many applications including climatology assessments for renewable energy projects, maritime engineering design, event‐based impact assessments, generating boundary conditions for further downscaling, amongst others. Here, we present a global wave hindcast with nested high‐resolution grids for the Exclusive Economic Zones of Australia and south west Pacific Island Countries, that is extended in time monthly. The model employs strategic methods to incorporate the effects of subgrid sized features such as small islands and islets. Various bulk wave parameters are available hourly from January 1979 to present, along with the full wave spectra at a set of 3, 683 predetermined points distributed globally. Abstract : Wind‐wave hindcast data have many applications including for renewable energy projects, maritime engineering design, impact assessments and producing boundary conditions for coastal models to better simulate the waves approaching the shore like shown in the image. Here, we present a global wave hindcast with nested high‐resolution grids for Australia and south west Pacific Island Countries, that spans from 1, 079 to present, updated monthly. The model employs strategic methods to incorporate the effects of subgrid sized features such as small islands and islets.